(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Consumption of alcoholic herbal products from beverages or medicinal drinks contaminated with heavy metals can cause serious consequences on human health. This is a major concern for traditional and herbal medicine. The present study was carried out to analyze and quantify the levels of seven potentially toxic heavy metals namely Magnesium, lead, cadmium, copper, iron, chromium and nickel in Action Bitter alcoholic herbal bitter. Twenty one ACTION BITTER alcoholic bitter samples were previously pretreated and homogenized were digested and analyzed to obtain a concentration of Cadmium (Cd), Chromium (Cr),Copper (Cu), Iron (Fe), Magnesium (Mg), Nickel (Ni) and lead (Pb) using atomic absorption spectrophotometer equipped with graphite tube atomizer. The concentration obtained are Cadmium (0.017 mg/l),Chromium (0.061 mg/l),Copper (0.056 mg/l), Iron (0.223 mg/l), Magnesium (1.118 mg/l), Nickel (0.112 mg/l) and lead (-0.073 mg/l). The analysis of heavy metals can be useful to evaluate the dosage of herbal drinks prepared from these plants. Therefore, it is of great importance to establish universal standards and quality requirements for hazardous elements in herbal drinks so that this natural resource can continue and expand further, to benefit health globally.